The Narrative Text as a Way to Strengthen the Communicative Competence of sfl - Aponte Buitrago, Andrea Lorena (Rastros Rostros, 2014)
This article presents various aspects of a research study into the teaching of Spanish as a Foreign Lan-guage (sfl), the objective of which was to strengthen the communicative competence of foreign sflstudents through the use of different narrative texts: fables, tales, myths and legends. The project aimedto revise, apply and design a reading workbook with various narrative texts, along with exercises andactivities. In terms of the methodology applied, this was an experimental study, and used an inductivemethod insofar as it involved the participation of a limited number of foreign students visiting Universidad Pedagógica y Tecnológica de Colombia (uptc) or the city of Tunja for both the application andanalysis of results. It was found that the strategy of using narrative texts (fables, tales, myths and legends) helped improve sfl . Likewise, the foreign students found the texts to be appropriate, and the activities and exercises to be dynamic
Keywords: communicative competence; tale; sfl; (Spanish as a Foreign Language); fable; legend; myth